Eksplorasi Dinamika Peminjaman Kata dalam Bahasa Arab Modern: Studi Kasus pada Bidang Teknologi dan Sains - Imam Wahyudi; Zainuri; Sulaiman, Muhammad (STAI Nurul Huda Kapongan Situbondo, 2024)
This research explores the dynamics of loanwords in modern Arabic, particularly in the fields of technology and science. Using a descriptive qualitative approach, this study identifies the types of loanwords, the mechanisms of linguistic adaptation, and their impact on Arabic usage. Data were collected through analyzing dictionaries and scientific articles. The findings show that borrowing words from English, such as